EGI (Education Of Egg Incubator) di Apit Aik Guna Revitalisasi Ekonomi Pasca Gempa - Septiawan, Adi; Rohmah, Rohmah; Sukirno, Sukirno; Murti, Baiq Dwi; Cahya, Ratna; Sumaeni, Baiq; Faresta, Rangga Alif (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2021)
Apit Aik hamlet is located in the thunder village of Tiger District Gunung Sari West Lombok Regency, NTB. Geographically, poultry farms in the hamlet are very potential with the enthusiasm of the majority who work as poultry farms. out of 126 family cards (KK), around 75% are farmers and farmers. However, the earthquake with a magnitude of 7.00 in the Richter in West Nusa Tenggara provides a bad impact on livestock. As a result, there are many people who have lost their jobs because the cages are damaged, livestock are suppressed and many animals die. To revitalize poultry farms in apit aik hamlets, farmers need a lot of capital and a considerable amount of time because the hatching method is still traditional, which is only capable of 30-60 items / parent / year. Therefore, EGI service (Education of Egg Incubator) in the Apit Aik hamlet it is a service that provides education to the apit aik hamlet farmers on how to incubate eggs in large quantities by applying egg hatching technology using egg hatching machines that are capable of hatching eggs from 150 to 200 eggs. This service is carried out by demonstration methods, and direct practices related to how to make egg hatching machines and egg hatching methods using egg incubator, so that the community can easily understand the material presented. This service is expected to help the apit aik hamlet revitalize their economy after the earthquake.Â Keywords: diversification, economic, kekait, palm